2019
DOI: 10.1097/md.0000000000014882
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk of surgical site infection after adult femoral neck fractures treated by surgery

Abstract: Surgical site infections (SSI) are devastating complications after surgery for femoral neck fractures. There are a lot of literature have shown a strong association between diabetic patients and SSI. This study aimed to identify diabetes as an independent risk factor of SSI, focusing on femoral neck fractures, and to investigate the other potential risk factors for SSI.We retrospectively collected data from patients who underwent surgery for femoral neck fractures through the medical record management system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
(47 reference statements)
1
22
0
3
Order By: Relevance
“…Femoral neck fractures usually occur following falls, which are very common in the geriatric population, accounting for 48.22% of hip fractures and 3.13% of all fractures in adults. 1 With ageing populations, an increase in the number of femoral neck fractures is inevitable; age-associated low bone mineral density, malnutrition and accompanying vitamin depletion, as well as the presence of other pre-existing risk factors, makes the geriatric population especially susceptible to fracture. There are a number of treatment options for fractures of the femoral neck, including hemiarthroplasty (HA), arthroplasty (THA), internal fixation and non-operative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Femoral neck fractures usually occur following falls, which are very common in the geriatric population, accounting for 48.22% of hip fractures and 3.13% of all fractures in adults. 1 With ageing populations, an increase in the number of femoral neck fractures is inevitable; age-associated low bone mineral density, malnutrition and accompanying vitamin depletion, as well as the presence of other pre-existing risk factors, makes the geriatric population especially susceptible to fracture. There are a number of treatment options for fractures of the femoral neck, including hemiarthroplasty (HA), arthroplasty (THA), internal fixation and non-operative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Chenni Ji et al performed a retrospective study of 692 patients with femoral neck fractures and also found that low HGB level is risk factor of SSIs. [30] These results indicate the importance of low hemoglobin levels in the development of SSIs. In high-risk patients with multiple risk factors, preoperative mandatory optimization should be considered.…”
Section: Risk Factorsmentioning
confidence: 84%
“…We identify femoral fractures and tibia and bula fractures as independent risk factors for surgical site infection of limb fractures, consistent with the infection rates we have observed in the previous literature. [29,30,37] The location of femoral fracture is deep, and the trauma caused to the body during the reduction of fracture is large, which may be the reason for the higher risk of infection after femoral fracture surgery. Besides, relatively longer bed time is usually required after femoral fracture surgey, which also increase the risk of SSI.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Among the risk factors associated with SSI occurrence, the most prevalent are those related to inadequate wound healing (smoking (12), old age (13), obesity, malnutrition ( 14 surgeries, operative time and type of anesthesia have also been described (17).…”
Section: Discussionmentioning
confidence: 99%